Immunotherapy of Guillain-Barré syndrome - Shuang Liu; Chaoling Dong; Eroboghene Ekamereno Ubogu (Taylor & Francis Group, 2018)
Guillain-Barré syndrome (GBS), the most common cause of acute neuromuscular weakness and paralysis worldwide, encompasses a group of acute immune-mediated disorders restricted to peripheral nerves and roots. Immune-mediated attack of peripheral nervous system myelin, axons or both is presumed to be triggered by molecular mimicry, with both cell- and humoral-dependent mechanisms implicated in disease pathogenesis. Good circumstantial evidence exists for a pathogenic role for molecular mimicry in GBS pathogenesis, especially with its axonal forms, providing insights that could guide future immunotherapy. Intravenous immunoglobulin (IVIg) and plasma exchange (PE) are the most commonly prescribed immunotherapies for GBS with variable efficacy dependent on GBS subtype, severity at initial presentation and other clinical and electrophysiologic prognostic factors. The mechanisms of action of IVIg and PE are not known definitely. Despite recent significant advances in molecular biology that provide insights into GBS pathogenesis, no advances in therapeutics or significant improvements in patient outcomes have occurred over the past three decades. We summarize the clinical aspects of GBS, its current pathogenesis and immunotherapy, and highlight the potential of leukocyte trafficking inhibitors as novel disease-specific immunotherapeutic drugs.